2023
DOI: 10.1017/s0047279422000794
|View full text |Cite
|
Sign up to set email alerts
|

To Claim or Not to Claim: Investigating Non-Take-Up of Welfare Schemes Targeting Hong Kong Older Adults and the Stigma Attached to Them

Abstract: This article investigates the unique contribution of specific programme characteristics together with personal stigma, stigmatisation by the public, and claims stigma, to the non-take-up of targeted income support among Hong Kong older adults. Drawing on data from a sample of 3,299 Hong Kong older adults aged 65 or above, we find that between 11-14 per cent of eligible participants did not receive cash transfers from Normal and Higher Old Age Living Allowance (OALA) and old-age Comprehensive Social Security As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Although I managed to get it (CSSA) at last, I still feel angry when I recall the process” (H1). This supports the existing literature on social services and welfare system issues that constitute obstacles for the elderly ( 32 , 59 ). While the elderly had to rely on social security to make a living, the welfare system is not applicant-friendly, which results in the needy elderly being barred from the financial support provided at the societal level.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Although I managed to get it (CSSA) at last, I still feel angry when I recall the process” (H1). This supports the existing literature on social services and welfare system issues that constitute obstacles for the elderly ( 32 , 59 ). While the elderly had to rely on social security to make a living, the welfare system is not applicant-friendly, which results in the needy elderly being barred from the financial support provided at the societal level.…”
Section: Resultssupporting
confidence: 89%
“…Such instances also occur in the Chinese context such as in Hong Kong where some of the elderly do not receive social assistance or security because they are not considered eligible applicants ( 32 ). As noted by Kühner and Chou ( 59 ), the costs and difficulties in the procedures for applying for social security constitute a barrier for the elderly to receive financial assistance from the Government. The level of welfare support received by the elderly appears to have cultural differences.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent times, a number of common stereotypes have been identified, leading to feelings of shame, fear of losing respect, reluctance to reveal assets and income, and fear of humiliation (Kühner & Chou, 2023). The role of prototypes in shaping ideas has shown that stereotypes can have a significant impact on this process.…”
Section: Cct In Comparative Perspectivesmentioning
confidence: 99%
“…Thus, a multi‐level institutional analysis of claimants' experiences displays actors' aggregated moves and meaning‐making processes in relation to the welfare systems (Gřundělová, 2021; Rice, 2013). As the recent research on welfare claimants' experiences in Chinese contexts focuses more on poverty stigma (Chan et al, 2022; Kühner & Chou, 2023; Li & Walker, 2017), a more institutional and contextual analysis is needed to link the meanings of surviving below the poverty line and accessing welfare at the street level (Fuertes & Lindsay, 2016).…”
Section: A Multi‐level Institutional Approach To Welfare Claiming Exp...mentioning
confidence: 99%